The tax collector and the priest: Matthew the Evangelist in the writings of Bede (c. 673-735) - Quigley, Emily (2023)
This thesis examines the use of Matthew the Evangelist and his Gospel in the writings of Bede (673-735), a theme which is unexplored in Bedan scholarship. An original quantitative methodology is employed to trace Bede’s interest in Matthew’s Gospel across the Bedan corpus. It is argued that Matthew is the most important book of scripture to Bede. This is within the context of Matthean primacy in patristic writings and Insular culture, but this thesis demonstrates that Bede adeptly shaped Matthew and his Gospel to suit his contemporary religious environment. Section one of this study establishes the context for Bede’s understanding of Matthew and his Gospel by assessing evidence of textual representations of Matthew in patristic writings (Chapter 1) and visual representations in Insular illuminated manuscripts (Chapter 2). Chapter 1 identifies that Augustine was the primary influence on Bede’s understanding of Matthew, moving away from scholarly emphasis on Bede’s debt to Gregory the Great.